PENGGUNAAN MINATO PADA MATA KULIAH PENGAJARAN BAHASA JEPANG DI POLITEKNIK TAKUMI - Aldilah Alifany Darrienda; Intan Hapsari; Julita Fahrul Rochim (Bajang Institute, 2025)
One of the graduate profiles of Takumi Polytechnic Japanese Language Diploma Program (Program Studi D3 Bahasa Jepang Politeknik Takumi) students is to become a Japanese language tutor at a non-formal institution. Thus, students need to be equipped with knowledge about Japanese teaching methods. Minato, a platform developed by The Japan Foundation, not only provides free Japanese language courses but also courses on Japanese teaching methods for Japanese language teachers. This course material is used for the taching material for the Metode Pengajaran Bahasa Jepang untuk Tingkat Menengah (Japanese Language Teaching Methods for Intermediate Level) course. This study aims to examine the use of Minato in the course. The results of this study found that students responded well and supported the reuse of Minato as a material in a series of Japanese language teaching lecturers in the Japanese Language Diploma Program at Takumi Polytechnic with some suggestions for improvement